Knowledge of Educational - Staff in Technical Institute of Karbala towards Ebola Virus Disease - Jasim, Balqees Sadoon; AL-Nasrawii, Maytham Salim; Al- Aaragi, Ali Neamah Hasan (International Journal of Psychosocial Rehabilitation, 2020)
Background: The Ebola Virus Disease (EVD) outbreak had dangerous consequences throughout the world, considering a major threat to public health. The current study assessed the information of educational- staff in the Technical Institute of Karbala towards Ebola Virus Disease.Subjects & Methods: Across sectional survey study using with an interviewer administered questionnaire. Data collected from a random sample of 200 educational staff in the Technical Institute of Karbala, regarding their knowledge about the Ebola Virus Disease. Statistical analysis done by using Chi-Square (χ2) test.Result: - For a total of all participants, who completed the questionnaire, more than half of the respondents (61%) had adequate knowledge. There was no significant difference in age groups with occupation, while there was high association (p-value < 0.05) in certificate, specialty and genders. Television is the first influencer (91%) on the information of participants.Conclusion: In spite of good knowledge level as in general, but we recommended to increase the understanding about how the disease can be transmission and prevented infection with EVD.